Successfulness of content marketing in tourism: The importance of instrument testing - Radenković-Šošić Bojana; Perić Dušan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2016)
Along with the improvement of the information technology, new means of communication in tourism were also developed, the success of which is not always easy to measure. The subject of this paper is based on researching the means of measurement of new communication forms, classified in today's marketing under the term of content marketing. A necessity to test the measuring instrument was observed when aiming to obtain more precise data on the successfulness of use of a form of content marketing in tourism. After a review of insights into measurement of successfulness of content marketing gained thus far, the paper demonstrates the process of testing of a measuring instrument (questionnaire) based on an empirical method, whose results should indicate the final form of the measuring instrument. The goal of the paper is to show the significance of this phase of research in the process of measurement of successfulness of marketing content.